The Relationship Between Organizational Trust and Organizational Silence: A Literature Review (UNWE Yearbook, 2024)
This study examines the relationship between trust in colleagues, supervisors, and management, and the dimensions of organizational silence, such as defensive and deafening silence, across different sectors and regions. By analyzing data from previous studies in education, industry, and services in countries like Indonesia, South Korea, Turkey, and Afghanistan, the study provides insights into how trust affects organizational silence. Using secondary data analysis, statistical methods were employed to explore these relationships. The findings show significant disparities based on sector and geographic location. For example, a strong inverse relationship was found between trust in colleagues and defensive silence in Indonesia's education sector, while no significant impact was observed in South Korea's service sector. Trust in supervisors also had a notable effect on organizational silence, with variations depending on the sector. The study highlights the role of cultural and managerial differences and offers recommendations to enhance trust and reduce organizational silence.